Interaction between a 101‾2 twin boundary and grain boundaries in magnesium. (March 2020) - Tang, Jing; Fan, Haidong; Wei, Dean; Jiang, Wentao; Wang, Qingyuan; Tian, Xiaobao; Zhang, Xu
Abstract: Deformation twinning is a common plastic deformation mode in polycrystalline magnesium (Mg), so the interaction between twin boundary (TB) and grain boundary (GB) plays an important role in the improvement of material strength and ductility. In this work, molecular dynamics (MD) method was employed to study the interaction between 10 1 ‾ 2 TB and GB. Four GB types were considered, i.e., symmetric tilt grain boundary (STGB), asymmetric tilt grain boundary (ATGB), basal twist grain boundary (BTGB, GB coincides with the basal planes of both grains) and prismatic twist grain boundary (PTGB, GB coincides the prismatic planes of both grains). MD simulations show that for both tilt GBs, the twin is able to penetrate through GB at small misorientation angle (<15°). At medium misorientation angle (15°–75°), the TB is absorbed by GB with stacking faults nucleated on the new GB, while at large misorientation angle (>75°), the TB is fully absorbed without any stacking faults. For twist GBs, the TB always penetrates through PTGBs, but is fully absorbed by BTGBs for all considered misorientation angles. All the GBs were observed to have a blocking effect on twinning deformation whether the twin penetrates through GB or not. Based on the interaction mechanisms mentioned above, we proposed an analytical twin thickening model via the Eshelby solutions to describe the GB strengthening effects or grain size effects on twinning, which shows that the material strength dominated by twinning is inversely proportional to the grain size. By comparison with the Hall-Petch model, we can see that the grain size effect on twinning deformation is stronger than that on dislocation slip, which agrees well with previous experimental observations. It is worth noting that this model would be valid for not only HCP (hexagonal close-packed) materials but also FCC (face-centered cubic) and BCC (body-centered cubic) materials. Current work provides new insights into the GB strengthening effects and grain size effects on twinning deformation. Highlights: Interaction between twin boundary and grain boundary was studied. Twin penetrates through grain boundary. Analytical model on grain size effect on twinning was proposed.